The role of GIS and remote sensing in tracking vegetation cover in the Tlagh and El-Abed Basins (Northeastern Morocco) from 1986 to 2018 - Mouadili Omar; Sbai Abdelkader (E3S Web of Conferences)
The Tlagh and El-Abed basins in the Taourirt-Guercif corridor are known for their diverse plant cover, especially in species naturally present for generations, termed 'inherited species'. However, this diversity needs to be more evenly distributed. Vegetation degradation is concentrated in the piedmonts and reliefs of both basins, attributed to topography, lithology, soil type, and climate. These formations, categorized into various types, all exhibit severe degradation due to persistent drought. Plant cover has decreased over time due to species disappearance or emergence of new formations adapted to drought conditions. This underscores the urgency of our research. This article discusses plant cover distribution and diversity in the El Abed and Tlagh basins and the evolution of plant cover density from 1986 to 2018. Our study, using Landsat satellite images, calculates seven vegetation indicators (GNDVI, GRVI, IPVI, SR, DVI, OSAVI, SAVI), showcasing our research precision.